Nutrient cycling and soil quality in threatened veredas in two Protected Areas of the Brazilian cerrado - Oliveira, Leliane R. D.; Frazão, Leidivan A.; Silva, Sabrina C. O.; Araújo, Walter S.; Nunes, Yule R. F.; Fernandes, Valquíria M.; Veloso, Maria D. M. (Nature Conservation Research: Заповедная наука, 2024)
Veredas are humid environments of significant importance for the Brazilian Cerrado. Understanding soil quality and ecological processes between the soil and vegetation in veredas can provide insights into ecosystem dynamics. This study was aimed to assess litter deposition and decomposition, as well as soil quality, including chemical, physical, and microbiological attributes, in two threatened veredas at various stages of conservation in Brazil. The research was conducted in Almescla (a preserved vereda) within the Environmental Protection Area of the River Pandeiros, and Peruaçu (a degraded vereda) located at the Veredas do Peruaçu State Park. Litter deposition was measured using collectors, and decomposition was assessed with litter bags. Soil granulometry, carbon and nutrient contents, and soil microbial biomass were also evaluated to a depth of 20 cm. The litter production was higher in Peruaçu, with the leaf fraction accounting for more than 70% of the total in both studied areas. The decomposition constant (kc) was higher in Almescla vereda. Nutrient concentrations followed a decreasing order of Ca > N > K > Mg > S > P in both areas. Peruaçu vereda exhibited higher levels of clay, available P, and Ca. Microbial carbon, total organic carbon, microbial quotient, and carbon stock were higher in Almescla, whereas the metabolic quotient was higher in Peruaçu. Our results suggest that the degradation of vereda ecosystems may lead to changes in nutrient cycling, with reduced litter deposition and decreased carbon storage.